Sanitation conditions as an epidemiologic indicator for American Cutaneous Leishmaniasis in the Brazilian Southwestern Amazonia - Ribeiro, Mateus Duarte; Ferraudo, Antonio Sergio [UNESP]; Zaia, Jose Eduardo; Andrade, Monica (Fundacao Oswaldo Cruz, Escola Politecnica Saude Joaquim Venancio, 2017)
This paper analyzes the relationship between sanitation and electricity service conditions, and American Cutaneous Leishmaniasis (ACL) in Acre. For this study we considered the cases reported in the Brazilian System for Disease Notification between 2001 and 2010, using the principal component analysis. The analysis suggested a direct association between ACL and inadequate housing characteristics - that worsen the occurrence of this disease-, such as: water supply in river or lakes, rainwater storage, disposal of solid waste dumped in vacant lots, and absence of electricity service, in rural areas; and absence of bathrooms and sanitation, in both urban and rural areas. An inverse association arises, mitigating the occurrence of ACL, in urban areas, by using septic tanks for sewage. The associations found in this study suggest that inadequate housing conditions contribute to increasing the population's exposure to vectors of ACL.
Keywords: American Cutaneous Leishmaniasis; Principal Component Analysis; Rural Sanitation; Urban Sanitation; Electricity